1999
DOI: 10.1096/fasebj.13.10.1219
|View full text |Cite
|
Sign up to set email alerts
|

Functional heterogeneity of osteoclasts: matrix metalloproteinases participate in osteoclastic resorption of calvarial bone but not in resorption of long bone

Abstract: Data in the literature suggest that site-specific differences exist in the skeleton with respect to digestion of bone by osteoclasts. Therefore, we investigated whether bone resorption by calvarial osteoclasts (intramembranous bone) differs from resorption by long bone osteoclasts (endochondral bone). The involvement of two major classes of proteolytic enzymes, the cysteine proteinases (CPs) and matrix metalloproteinases (MMPs), was studied by analyzing the effects of selective low molecular weight inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
102
1
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(117 citation statements)
references
References 44 publications
11
102
1
3
Order By: Relevance
“…Osteoclasts were isolated as described before (25). Briefly, long bones were dissected from 5-d-old Chinchilla rabbits, and the periostea were removed.…”
Section: Osteoclast Activity Assay Using Rabbit Osteoclastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoclasts were isolated as described before (25). Briefly, long bones were dissected from 5-d-old Chinchilla rabbits, and the periostea were removed.…”
Section: Osteoclast Activity Assay Using Rabbit Osteoclastsmentioning
confidence: 99%
“…In addition, AZD0530 is the first Src inhibitor to show inhibition of the Src pathway in human tumor tissue (22). Preliminary data suggest that AZD0530 could specifically affect osteoclastic bone resorption because resorption markers present in serum and urine were significantly reduced after single (volunteers) or multiple daily doses of AZD0530 (volunteers and patients with cancer), whereas markers for bone formation were not affected (23)(24)(25). AZD0530 is now being tested specifically in cancer patients with metastatic bone disease to determine its effect on bone turnover markers in this population (22).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitor studies of bone resorption also suggested a distinct role for one or more MMPs which was dependent on bone type (Everts et al, 1999). Further studies have implied that MMP-mediated collagen proteolysis may be physiologically important in removing any remaining matrix from areas vacated by osteclasts at the end of the resorption cycle (Everts et al, 2002).…”
Section: Bone: Altered Metabolism and Extracellular Matrix Proteolysismentioning
confidence: 99%
“…Важная роль в разрушении и ремоделировании тканей отводится матриксным металлопротеазам (MMП), однако сведения об их участии в резорбции кости весьма противоречивы. Установлено, что MMП-1,-2 продуцируются остеобластами [3,8]. У мышей, нокаутированных по различным ММП, не обнаружено изменений резорбции кости [4] или найдены лишь незначительные кратковременные изменения в деградации костной ткани [3].…”
unclassified
“…У мышей, нокаутированных по различным ММП, не обнаружено изменений резорбции кости [4] или найдены лишь незначительные кратковременные изменения в деградации костной ткани [3]. С другой стороны, на культуре остеокластов показано, что ММП-9 (желатиназа В) также необходима для резорбции костей черепа, как и катепсин К [8]. Вовлеченность изменений матриксных металлопротеаз в патогенез остеопороза изучена недостаточно.…”
unclassified